Meninjau Respon Masyarakat Terkait Pemenuhan Hak Ekosob Melalui Kebijakan Protokol Kesehatan di Masa Pandemi: Reviewing Community Responses Regarding the Fulfillment of Ecosob Rights through Health Protocol Policies during the Pandemic - Cahyani, Anisa; Putri, Awallia Septiyana (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The enforcement of socio-economic rights based on the constitution during this pandemic era is unnegotiable. The government with its authority through various health protocol (prokes) policies is realizing the protection of those rights. Unfortunately, many problems arise during the implementation of the existing rules. Both in the terms of the goverment and the community factors, they have a big role in order to follow the main policies issued especially during this pandemic era. The benchmark for the success of these policies are influenced by the firmness of the rules and the action that is come from the government. Futhermore, from the side of the community, the faith to the government, the level of legal understanding, and the cultural factors play a major role in measuring the success of these policies. The method that is used in this research is normative-juridical regarding implementation of the rules related to the health protocols during the Covid-19 pandemic with qualitative data processing to draw conclusions about the circumstances that occurred. The goals of this paper can be used to describe, explain, and analyze patterns of community behavior towards government policies during the pandemic era and to find out the source of all the problems in purpose for improving and providing criticism and suggestions based on existing mistakes.